Pharmaceutical Excipients: Functions, Selection Criteria, and Emerging Trends - Makkad, Saniya; Sheikh, Mujibullah; Shende, Sanskruti; Jirvankar, Pranita (International Journal of Pharmaceutical Investigation, 2025)
Pharmaceutical excipients are integral to therapeutic formulations; their importance has grown from inert and economical materials to components that make up 80-90% of the finished product. This review examines the excipient classification scheme developed by the International Pharmaceutical Excipient Council (IPEC) and the process by which safety evaluation criteria are set for newly suggested excipients. It also highlights how excipients impact the price, effectiveness, and stability of medications, especially when used in solid dosage forms. The study also addresses new developments in excipient functionality and utilization, highlighting the need for multifunctional excipients to improve pharmacological efficacy, stability, and affordability. The purpose of this article is to shed light on the roles that pharmaceutical excipients play in the efficacy of medication formulations by examining their functions, selection criteria, and developing trends.
Keywords: Pharmaceutical Excipients; Formulations; Active pharmaceutical ingredient (API); Excipient selection; Interactions